(untitled) (Orfeu, 2016)
After resounding success of Il Guarany and the controversies generated by his audacious Fosca, Antônio Carlos Gomes, now well experienced in two different models, the grand opera tradition in the former and the inovation in the latter, puts on the stage his Salvator Rosa (1874), using standard procedures of structure and musical composition. Despite this return to the conventions, we see greater freedom of writing to the brass’ section from the composer, giving them unusual roles for the old school melodramma. First elucidating the role of brass in theater orchestras from the main treatises of instrumentation and orchestration studied in Italy at the end of the first half of the nineteenth century, the work also aims to present the cimbasso – common term in the works of Gomes and representative of the low range of the brass instruments in his orchestra. Using as methodology the analysis of treatises of instrumentation, orchestration and texts of the Gazetta Musicale di Milano, the work contextualizes the instrumental tradition operated by Gomes to the composition of his Salvator Rosa at the same time presenting an eloquent writing mode for the section of the brass, approaching the instrumental apparatus that vocal usual. Because of the discrepancy of the editions found, the scanned original manuscript of the opera was the main source consulted.